O NOUĂ VIZITĂ, NOI PRACTICI ȘI OPORTUNITĂȚI PENTRU MODERNIZAREA BIBLIOTECILOR - GUMENI, șef serviciu copii, Filiala polonă „A. Mickiewicz”, Svetlana (BIBLIOPOLIS, 2020)
10 young librarians from the Republic of Moldova, who benefited from a travel grant from the Novateca Program, having the opportunity to visit county libraries in Romania that have exceeded their status and have a clear position in the community. If at the beginning of the visit some of the participants were skeptical, at the end of the visit, everyone was determined to bring the changes to the library they represent, to prove the importance of their profession, libraries in the community.